2019
DOI: 10.1124/jpet.119.258129
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of TrkB Expression and Signaling by Valproic Acid and Other Histone Deacetylase Inhibitors

Abstract: Valproic acid (VPA) has been shown to regulate the levels of brain-derived neurotrophic factor (BDNF), but it is not known whether this drug can affect the neuronal responses to BDNF. In the present study, we show that in retinoic acid-differentiated SH-SY5Y human neuroblastoma cells, prolonged exposure to VPA reduces the expression of the BDNF receptor TrkB at the protein and mRNA levels and inhibits the intracellular signaling, neurotrophic activity, and prosurvival function of BDNF. VPA downregulates TrkB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…Thus, the VPA-induced changes observed in the present study may have clinical relevance when the drug is used to treat extra-cranial tumours, such as neuroblastoma. Moreover, within the same concentration range VPA was previously found to cause hyperacetylation of H3 histone and downregulation of TrkB in SH-SY5Y cells [ 57 ], indicating that the drug can induce chromatin remodelling and altered expression of neurotrophin receptors with similar potencies.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Thus, the VPA-induced changes observed in the present study may have clinical relevance when the drug is used to treat extra-cranial tumours, such as neuroblastoma. Moreover, within the same concentration range VPA was previously found to cause hyperacetylation of H3 histone and downregulation of TrkB in SH-SY5Y cells [ 57 ], indicating that the drug can induce chromatin remodelling and altered expression of neurotrophin receptors with similar potencies.…”
Section: Discussionmentioning
confidence: 80%
“…Relatively little is known on the control of SORT1 gene expression and the precise molecular mechanisms linking HDAC inhibition and sortilin upregulation remain to be elucidated. Nonetheless, the observation that the HDAC6 inhibitor tubacin and the HDAC8 inhibitor PCI-34,051, which do not induce histone hyperacetylation [38,39,57], had no effects on either sortilin or p75NTR expression indicates that both responses are not induced by generic HDAC inhibition but involve specific HDAC isoforms capable of producing chromatin remodelling. Immunoprecipitation experiments indicated that in VPA-treated SH-SY5Y cells the upregulation of p75NTR and sortilin expression was accompanied by an enhancement of proNGF-induced association of the two receptor proteins and potentiation of JNK activation, as indicated by the increased phosphorylation of JNK and c-Jun.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is reported that inhibition of enhancer of zeste homolog 2 (EZH2) contributes to the antitumor effect of HDAC inhibitor in neuroblastoma cells and lung cancer cells [28,29]. EZH2 is the functional core subunit of the polycomb repressive complex 2 (PRC2), and plays a pivotal role in catalyzing the methylation of the lysine 27 of histone H3 (H3K27) [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%